Assessment and Quantification of Methane Emission from Indian Livestock and Manure Management - Anuja Samal; Saroj Kumar Sahu; Ashirbad Mishra; Poonam Mangaraj; Shantanu Kumar Pani; Gufran Beig (Aerosol and Air Quality Research)
Abstract Methane (CH4) is one of the most abundant organic trace gases in the atmosphere having a strong global warming potential of 28 in 100 years, is a significant GHGs, and has a vital role in atmospheric chemistry and climate change. India is home to the largest number of livestock in the world and is responsible for higher methane emissions from enteric fermentation and manure management. In the present study, the methane emissions from Indian livestock, i.e., enteric fermentation, is estimated to be 11.63 Tg yr–1 in 2019 using IPCC methodology and recent census livestock activity data from the Department of Animal Husbandry and Dairying, Government of India, and corresponding country-specific revised emission factors. The CH4 emissions from livestock manure management system is found to be 1.11 Tg yr–1, resulting in 12.74 Tg yr–1 of CH4 emission from the Indian livestock sector. The district-level spatial CH4 emission pattern is developed to identify the potential emission hotspots across the country. Initial findings suggest that changing livestock population patterns plays an important role in governing methane emissions in rural India. The information generated could be important tools for policymakers to control CH4 emissions across the country.